Spin within systematic review abstracts on antiplatelet therapies after acute coronary syndrome: a cross-sectional study. Issue 8 (2nd August 2022) - Wise, Audrey; Mannem, Deepika; Arthur, Wade; Ottwell, Ryan; Greiner, Benjamin; Srouji, Derek; Wildes, Daniel; Hartwell, Micah; Wright, Drew N; Khojasteh, Jam; Vassar, Matthew
Abstract : Objectives: Spin is a reporting practice in which study results are misrepresented by overestimating efficacy or underestimating harm. Prevalence of spin varies between clinical specialties, and estimates are based almost entirely on clinical trials. Little is known about spin in systematic reviews. Design: We performed a cross-sectional analysis searching MEDLINE and Embase for systematic reviews and meta-analyses pertaining to antiplatelet therapies following acute coronary syndrome on 2 June 2020. Data were extracted evaluating the presence of spin and study characteristics, including methodological quality as rated by A MeaSurement Tool to Assess systematic Reviews (AMSTAR-2). All data extraction was conducted in a masked, duplicate manner from 2 June 2020 to 26 June 2020. Participants and setting: Not applicable. Primary and secondary outcome measures: We assessed abstracts of systematic reviews on antiplatelet therapy following acute coronary syndrome and evaluated the prevalence of the nine most severe types of spin. We additionally explored associations between spin and certain study characteristics, including quality. Results: Our searches returned 15 263 articles, and 185 systematic reviews met inclusion criteria. Of these 185 reviews, 31.9% (59/185) contained some form of spin in the abstract. Seven forms of spin (1, 2, 3, 4, 5, 7 and 9) among the nine most severe were identified. No instances of types 6 or 8 were found. There were no statistically significant relationships between spin and the evaluated study characteristics or AMSTAR-2 appraisals. Conclusions: Spin was present in abstracts for systematic reviews and meta-analyses; subsequent studies are needed to identify correlations between spin and specific study characteristics. There were no statistically significant associations between spin and study characteristics or AMSTAR-2 ratings; however, implementing changes will ensure that spin is reduced in the field of cardiology as well as other fields of medicine.